2016
DOI: 10.1016/j.chest.2016.08.1123
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Therapy in Patients Undergoing EBUS-TBNA: Risk vs Benefit

Abstract: PURPOSE: Endobronchial ultrasound with transbronchial needle aspiration (EBUS-TBNA) has improved the ease with which practitioners can obtain mediastinum tissue samples. However, evidence-based studies are limited regarding best management of dual antiplatelet agents (DAPT) aspirin and clopidogrel, or clopidogrel alone in patients who undergo this procedure. One 2006 study recommended discontinuation of clopidogrel prior to transbronchial biopsy after documenting increased bleeding severity in patients taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In total, 8.7% of patients on dual antiplatelet therapy and 7.7% on clopidogrel had bleeding events, compared with a rate of only 2.9% for patients not on antiplatelet therapy. 10 The lack of statistical significance in this study may be attributed to its small sample size.…”
mentioning
confidence: 72%
“…In total, 8.7% of patients on dual antiplatelet therapy and 7.7% on clopidogrel had bleeding events, compared with a rate of only 2.9% for patients not on antiplatelet therapy. 10 The lack of statistical significance in this study may be attributed to its small sample size.…”
mentioning
confidence: 72%
“…Overall bleeding events were low, occurring in 2.9% of all patients, 8.7% for patients on both aspirin and clopidogrel, 7.7% for clopidogrel alone, <1 % for aspirin alone and 2.9% for patients not on any antiplatelet therapy. The difference was not statistically significant (P=0.164) (8). Another series reported twelve cases of EBUS-TBNA procedures performed on patients taking clopidogrel.…”
Section: Peri-procedural Management Of Antiplatelet Therapy In Electimentioning
confidence: 86%
“…12 In addition, others reported on the safety of thoracotomy when performed on patients taking clopidogrel. 12,16,17 Further, Stather et al 13 in a retrospective single center review of 12 cases, reported no significant bleeding with similar gauge needles. In the latter study, patients were followed for 30 days postprocedure.…”
Section: Discussionmentioning
confidence: 97%